Structural and cuantitative aspects of the ovary of the Fulica armillata (Aves: Rallidae) - Bulfon, Mirian (2011)
Morfohistologic and quantitative aspects were studied of the ovary of the Fulica armillata during gonadal recrudescence phase. Were used 5 adult females. Morfohistologic analysis revealed the presence of numerous follicles at different stages of development and regression. The simple epithelium of granulosa cells characterized the primary oocytes and the pseudostratified granulosa cells the previtellogenic follicle, both types showed a marked Balbiani body. In the white and yellow vitellogenic follicles > 1 mm evidenced a complex follicular wall formed by the radiated area, stratified follicular epithelium and well-defined thecal enveloped, while the vitellogenic yellow > 3 mm, was observed a simple epithelium with basophilic cuboidal cells. We identified two types of follicular atresia:1)intact follicle wall or non-bursting, the involution takes place inside the follicle,comprising the lipoidal atresia (primary oocytes) and lipoglandular (previtellogenic and vitellogenic follicles small), 2) atresia by wall rupture or bursting (vitellogenic follicles> 1 mm), extrusion of the yolk. Quantitative analysis revealed a statistically significant difference (p <0,05) among the developing follicles <2 mm and larger follicles and the same difference between the small atretic follicles (lipoidal and lipoglandulares) and bursting follicles. The processes of growth and differentiation (folliculogenesis and vitellogenesis) and follicular atresia develop normally during the gonadal recrudescence, contributing to the homeostasis of the ovary of this bird.